2014
DOI: 10.1590/1807-55092014000400545
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos de diferentes intensidades de exercício sobre a concentração sérica de interleucinas

Abstract: ResumoO presente estudo teve como objetivo analisar os efeitos agudos e de curta duração de duas intensidades de exercício aeróbio sobre a concentração circulante de IL-6 e IL-10. Quinze homens jovens fi sicamente ativos (21,0 ± 1,9 anos) foram submetidos a duas sessões de exercício ("crossover"): alta intensidade de exercício (AIE)-(80% VO 2 pico), e baixa intensidade de exercício (BIE)-(40% VO 2 pico), com intervalo de sete dias ("Wash out"). Amostras de sangue foram coletadas em tubos com EDTA, antes do exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
2
4
1
1
Order By: Relevance
“…Contrary to our hypothesis, IL-10 faced a significant 228% reduction in the 65-70% HR session. (Figure 3-B) There was a tendency (p = 0.053) for differences to occur between the variation delta between the 65-70% and the 80-85% HR sessions, a result compatible with another study mentioned above, 2 in which there was a decrease in IL-10 in the lower intensity session compared to the higher intensity session. These results suggest that borderline values of the same aerobic exercise intensity can produce different immune responses.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Contrary to our hypothesis, IL-10 faced a significant 228% reduction in the 65-70% HR session. (Figure 3-B) There was a tendency (p = 0.053) for differences to occur between the variation delta between the 65-70% and the 80-85% HR sessions, a result compatible with another study mentioned above, 2 in which there was a decrease in IL-10 in the lower intensity session compared to the higher intensity session. These results suggest that borderline values of the same aerobic exercise intensity can produce different immune responses.…”
Section: Discussionsupporting
confidence: 89%
“…In a study conducted with 20 physically active individuals, IL-6 increased in the high intensity session compared to the low intensity session. 2 However, our results showed that IL-6 did not vary between the pre-and post-exercise periods in both sessions (65-70% HR and 80-85% HR), neither in the comparison between one session and another, as Figure 3-A shows.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…This study also found that serum IL-6 levels presented significant acute changes in response to moderate intensity physical exercise (55% VO 2peak ). A single treadmill exercise session resulted in acute elevations of circulating IL-6, supporting the effects of physical exercise on the serum concentrations of this interleukin 21 .…”
Section: Discussionmentioning
confidence: 61%
“…O equilíbrio entre a concentração circulante de citocinas pró e antiinflamatórias é considerado um importante meio de controle da inflamação crônica, estando condicionado por regulação genética e estilo de vida. 31 O tamanho da amostra foi um fator limitante neste estudo. Apesar de a comunidade da Granja do Torto ser pequena e contar com 149 idosos, um maior número de indivíduos sedentários poderia dar uma visão mais ampla do quadro de sarcopenia nessa população.…”
Section: Sarcopênicosunclassified